Elementary Geometry for College Students (7th Edition) Clone

Published by Cengage
ISBN 10: 978-1-337-61408-5
ISBN 13: 978-1-33761-408-5

Chapter 6 - Review Exercises - Page 316: 34

Answer

EB = 6 FC = 7 AD = 3

Work Step by Step

We know that AD and AF are equal, so we know: $ 10 - FC = 9 - BD$ We also know that EC equals FC, so: $ 10 - AF = 13 - BE$ Finally, we know that BD equals BE. From these, it follows that EB must be 3 more than AF. Thus, we call AF the variable y to obtain: $EB = 3 + y$ $ BD = EB = 9 - y$ We solve for y: $ 3+y = 9 -y \\ y = 3$ Thus: $EB = 3 + 3 = 6$ $ AD = AF = y = 3$ $FC = 10 - y = 10 -3 = 7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.